The Diab-L - Schroeder, Paul (European Journal of Applied Sciences, 2023)
Many ‘advances’ by science have shifted knowledge back and forth over the life of mankind. Similarly, the lives, relationships, religion, etc. of people flowed throughout our history as time has advanced. Our early history was documented within the Bible. A view of the flow of science is needed and herein documented and conveyed to us by: The Holy Ghost - Oical